Red riječi u hrvatskom i poljskom jeziku: poteškoće s kojima se susreću poljski studenti kroatistike pri usvajanju reda riječi u hrvatskom jeziku - Podboj, Martina (Institut za Hrvatski Jezik i JezikoslovljegZagreb [Tb1]. Rasprave. - Zagreb : Institut za hrvatski jezik i jezikoslovlje, 1968-. - Online-Ressource. - ISSN 1849-0379 39, 2014)
Croatian and Polish are flective Slavic languages, both of which exhibit free word order. Second language acquisition research shows that the word order is much more influenced by native and/or first language of the learner, than any other linguistic feature. This suggests that Polish learners of Croatian will acquire Croatian word order without difficulty, due to similarities between the two languages. However, there is a significant amount of errors made by Polish students of Croatian, most of which, as would be expected, are wrong clitics positioning. Still, there are many errors caused by negative transfer from Polish. This paper shows the results of a small research conducted on students of Croatian at the University of Silesia in Katowice (Sosnowiec) and Adam Mickiewicz University in Poznań (3rd, 4th, and 5th year), where the author had spent time as a Croatian lecturer trainee and as an exchange student within the Erasmus programme. The reason for conducting such a research was the growing need for feedback which would help students avoid further errors, as well as enrich the process of learning Croatian syntactic rules. The analysis showed a need for a further investigation of the topic since error analysis gives only a partial insight to the problem, but can be indicative. Such investigation would help analyse and systematise errors more precisely, choose the most applicable second language acquisition theoretical framework, and identify reasons why negative word order transfer occurs. Since there are 5 Croatian language departments within Polish universities, such a study would enrich the study of Croatian as a foreign language in Poland significantly, which makes the pedagogical implications of this research far-reaching.